2013
DOI: 10.1016/j.addbeh.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cessation in African American light smokers enrolled in a bupropion clinical trial

Abstract: Background This is the first study to examine predictors of successful cessation in African American (AA) light smokers treated within a placebo-controlled trial of bupropion. Methods We analyzed data from a randomized, double-blind, placebo-controlled trial of bupropion and health education for 540 African American light smokers. African American light smokers (≤ 10 cigarettes per day, cpd) were randomly assigned to receive 150mg bid bupropion SR (n=270) or placebo (n=270) for 7 weeks. All participants rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…Evidence suggests that older age and markers of lower cigarette dependence are predictive of success 2, 3, 4, 5, 6, although not all studies show these results 7. There is less consistent, conflicting or negative evidence on the effects of age of smoking onset 2, 3, substance use disorder 8, psychiatric disorder 6, 9, gender 4, 6, 10, geographical location 11, 12, body mass index (BMI) 2, 3, 10, 13, 14 and prior use of smoking cessation treatments 15. These covariates were assessed in the EAGLES trial.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence suggests that older age and markers of lower cigarette dependence are predictive of success 2, 3, 4, 5, 6, although not all studies show these results 7. There is less consistent, conflicting or negative evidence on the effects of age of smoking onset 2, 3, substance use disorder 8, psychiatric disorder 6, 9, gender 4, 6, 10, geographical location 11, 12, body mass index (BMI) 2, 3, 10, 13, 14 and prior use of smoking cessation treatments 15. These covariates were assessed in the EAGLES trial.…”
Section: Introductionmentioning
confidence: 98%
“…Research investigating their influence among racial/ethnic minorities is limited. Faseru et al [23] was the first to investigate predictors of smoking abstinence among African Americans enrolled in an RCT testing the efficacy of bupropion. They found that treatment with bupropion was positively predictive of shortterm (week 7), but not longer-term (week 26) abstinence.…”
Section: Factors Associated With Smoking Cessation Among Racial/ethnimentioning
confidence: 99%
“…Studies suggest that persons with a lower NMR have better success at quitting than smokers with a higher NMR, [34][35][36] while other studies show no differences in quit rates 37 and no difference in the NMR in persons who quit compared with continued smokers. 38 Since the NMR has been proposed as a valid biomarker for predicting quitting success, 26,34 then understanding this biomarker as it relates to menthol smoking, which increases nicotine dependence and quitting difficulty, 10,11 is critically important.…”
Section: Nicotine Metabolism In Young Adult Daily Menthol and Nonmentmentioning
confidence: 99%